Different characteristics of a single sinonasal inverted papilloma from sequential PET-CT: A case report. Issue 52 (December 2017) - Kim, Jong Seung; Kwon, Sam Hyun
Abstract: Rationale: Inverted papilloma (IP) is a benign tumor that should be monitored carefully because it frequently recurs and has the potential to become malignant. Patient concerns: : We report a case of a 59-year-old woman who presented with a mass which had been found incidentally on positron emission tomography computed tomography (PET CT). Diagnoses: Using endoscopy and CT, the preoperative diagnosis was inverted papilloma. PET CT showed a mass with hot uptake in the left ethmoid and frontal sinus (maximum standardized uptake value (SUVmax) = 7.80). Interventions: We performed endoscopic sinus surgery (ESS) using 4 mm 0° and 70° endoscopes under general anesthesia. After 15 months of follow-up, remnant masses existed in the left frontal and supraorbital ethmoid cells. In the second PET CT taken at this time, a mass with lower SUV compared to the preoperative PET was observed in the lateral side of the left frontal sinus (SUVmax= 1.71). Revision ESS was performed using the "above and below" technique. Outcomes: Two years after initial surgery, follow-up CT showed there was no tumor recurrence in the frontal sinus or supraorbital ethmoid cell. There were no complications such as numbness in the forehead area after the operations. Conclusion: If the tumor is located at a site that is difficult to reach with an endoscope alone, it is faster and less painful to choose a more convenient approach for the patientand it can avoid unnecessary cost burden. It should also be noted that the SUV of PET is not a tool to distinguish IP from other inflammatory polyps or cancer.